Pemodelan UML Sistem Keamanan Berbasis Amplop Digital untuk Memenuhi Layanan Keamanan - Insan, Isa Mulia; Husen, Jati Hiliamsyah; Yasirandi, Rahmat (The Indonesian Journal of Computer Science, 2025)
This research focuses on the development and systematic redesign of a Unified Modeling Language (UML) model to represent a digital envelope-based security system. The digital envelope method, integrating both symmetric and asymmetric encryption, is employed to leverage the strengths of each encryption type, ensuring performance and security in data protection. The study enhances a previously proposed UML model by incorporating security symbols and notations tailored for security modeling, effectively capturing encryption principles while ensuring clarity and accuracy. However, several limitations were identified, particularly the lack of detailed separation between the encryption and decryption processes, which are crucial for ensuring data integrity, confidentiality, and non-repudiation. The research concludes that further development is required to refine these notations, including a clear distinction between encryption and decryption stages, and the inclusion of more detailed symbols for key management. Future work should focus on extending the notations to better address the security challenges faced by digital envelope-based systems, enhancing their representation of key generation, storage, and distribution